HYPOGLYCEMIA POTENTIAL OF ETHANOL EXTRACT OF MELINJO LEAVES (Gnetum gnemon L.) ON WISTAR MALE WHITE RATS - Herlina, Herlina; Dina Permata, Wijaya; Viva, Starlista; Annisa, Amriani; Herin, Noviarny (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2025)
Male rats were used in the study to evaluate the ethanol extract of melinjo leaf (Gnetum gnemon L.) for hypoglycemia after being given alloxan and having their pancreatic histology observed. Secondary metabolites with antidiabetic properties found in melinjo leaf include flavonoids, tannins, saponins, and phenolics. This study sought to ascertain the ethanol extract of melinjo leaves' ED50 as well as its impact on lowering blood glucose levels and monitoring pancreatic histology. The doses of melinjo leaf ethanol extract were varied to 125, 250, and 500 mg/kgBW. An insulin dosage of 1 IU/kgBW served as the positive control, a 0.5% Na CMC suspension served as the negative control, and a normal control group did not receive any therapy. Rats were tested by utilizing a DTN-410-K photometer to measure their fasting blood glucose levels on days 0, 10, 15, and 20 using the GOD-PAP enzymatic method. Hematoxylin-eosin staining was used in histopathology preparations, which were prepared in accordance with established protocols. Melinjo leaf ethanol extract dosages of 125, 250, and 500 mg/kgBW resulted in three treatment groups with corresponding the percentage of blood glucose reduction (%BGR) of 31.48, 34.39, and 42.90%, whereas the positive control had an average BGR of 40.68%. Melinjo leaf ethanol extract has an ED50 of 720.86 mg/kgBW. According to the histological image, the positive control group and the three treatment groups showed improvement, whereas the negative group's Langerhans islet endocrine cells showed necrosis. The 500 mg/kg BW dosage group shows the greatest improvement.